A-44 Experiences of Adversity and Validity of Baseline Concussion Testing. (13th July 2022) - Sorensen, A; Salas Atwell, M; Koroukian, S; Bailey, C; Briggs, F
Abstract: Purpose: This study examined the relationship between individual-level experiences of social adversity and baseline computerized concussion testing validity (Immediate Post-Concussion Assessment and Cognitive Testing; ImPACT). Methods: This study involved 6495 student-athletes born between 1995 and 2005 who completed a baseline ImPACT test between 10 and 18 years old and could be identified in the Child-Household Integrated Longitudinal Data (CHILD) System, a continuously updated integrated and comprehensive data system that captures detailed individual-level demographic, social service usage, and educational outcomes on every child born or living in Cuyahoga County, Ohio from 1989 to present. Multivariable logistic regression models were conducted with experiences of SNAP/TANF enrollment, substantiated abuse or neglect incidents, and extreme neighborhood deprivation occurring in the sensitive developmental periods of early childhood and adolescence as key predictors of baseline test validity. Results: Our findings suggest that social mobility may play an important role in baseline validity. Youth with upward social mobility (poverty or neighborhood deprivation in early childhood only) were not significantly different than youth without such experiences (OR = 0.91, p = 0.74). Youth with persistent adversity across childhood or downward social mobility (poverty or high neighborhood deprivation in adolescence only) had 50–72% lower odds of achieving a valid baseline test (persistent poverty: OR = 0.59, p = 0.05; adolescent poverty only: OR = 0.50, p = 0.004; adolescent neighborhood deprivation only: OR = 0.28, p < 0.0001). Conclusions: These findings suggest certain patterns of social adversity may predispose youth to invalid computerized concussion baseline testing scores, potentially increasing their risk of inaccurate injury management and poor outcomes.